Book Reviews (Blackfriars, 1926)
Book Reviews in this Article The Life and Times of Bishop Ullathorne (1806–1889). By Dom Cuthbert Butler. Two vols. The Constitution of the Dominican Order, 1216 to 1360. By G. R. Galbraith, M.A., Ph.D. The Spiritual Works of Abbot Blosius. Edited by Dom Roger Hudleston, O.S.B. Vol. 1. A Book of Spiritual Instruction. Vol. 2. Comfort for the Faint-hearted. Translated by Bertrand A. Wilberforce, O.P. An Anthology of Catholic Poets. Compiled by Shane Leslie. Memoirs of Sir Thomas Fowell Buxton, Bart. With introduction by Lord Buxton (London, J. M. Dent and Sons, 1925; Everyman Library, Vol. 773.) Lives of the English Poets. By Samuel Johnson, LL.D. With Introduction, 2 Vols. St. Joan of Arc. A Study of the Supernatural in her Life and Mission. By the Chanoine Justin Rousseil. Translated by the Rev. Joseph Murphy, S.J. Saint Radegund. By F. Brittain, M.A. Mary Aloysia Hardey. Religious of the Sacred Heart, 1809–1886. By Mary Garvey, R.S.C.J. With an Introduction by Rev. Thomas J. Campbell, S.J.